"It's Like Playing with a Nuclear Bomb": Fear, Accommodation, and the Nationalist Rhetoric of Evangelical Purity Culture. Issue 3 (7th April 2014) - Moslener, Sara
Abstract : Most observers of the evangelical purity culture situate it within a form of contemporary evangelicalism that prioritizes personal spiritual growth and self-fulfillment. As a result, portrayals of the movement emphasize the therapeutic individualism and optimism of new paradigm spirituality. But the new paradigm does not help us explain the language of spiritual warfare and what Jason Bivins calls a religion of fear within purity rhetoric. Evangelical purity culture is as equally informed by a religion of accommodation and new paradigm spirituality as it is by a religion of fear and the remnants of cold war fundamentalism. This discordance makes sense only when the contemporary purity culture is placed within a broader historical trajectory that marks its genesis in the fundamentalist resurgence of the 1940s, not the 1970s when new paradigm churches first emerged. By examining the seemingly discordant elements of evangelical purity culture, historians are able to recognize the theological and historical continuity between evangelicalism's religion of fear and religion of accommodation.